Safety and survival of docetaxel and cabazitaxel in metastatic castration‐resistant prostate cancer. (29th July 2021) - Kreis, Kristine; Horenkamp‐Sonntag, Dirk; Schneider, Udo; Zeidler, Jan; Glaeske, Gerd; Weissbach, Lothar
Abstract : Objectives: To investigate real‐world haematological toxicity, overall survival (OS) and the treatment characteristics of docetaxel and cabazitaxel chemotherapy in metastatic castration‐resistant prostate cancer (mCRPC). Patients and Methods: This retrospective claims data study followed patients with mCRPC receiving cabazitaxel or docetaxel from their first chemotherapy infusion. Haematological toxicities were measured using treatment codes and inpatient diagnoses. OS was estimated using the Kaplan–Meier method. A multivariable Cox regression analysis was used to identify OS predictors. Results: Data from 539 patients administered docetaxel and 240 administered cabazitaxel were analysed. Regarding adverse events, within 8 months of treatment initiation, some kind of treatment for haematological toxicity was documented in 31% of patients given docetaxel and in 61% of patients given cabazitaxel. In the same period, hospitalization associated with haematological toxicity was documented in 11% of the patients in the docetaxel cohort and in 15% of the patients in the cabazitaxel cohort. In the docetaxel cohort, 9.9% of patients required reverse isolation and 13% were diagnosed with sepsis during hospitalization. In the cabazitaxel cohort, the cumulative incidence was 7.9% and 15%, respectively. The median OS was reached at 21.9 months in the docetaxel cohort and, because of a later line of therapy, at 11.3 months in the cabazitaxel cohort. A multivariate Cox regression revealed that indicators of locally advanced and metastatic disease, severe comorbidities, and prior hormonal/cytotoxic therapies were independent predictors of early death. Conclusion: Cabazitaxel patients face an increased risk of haematological toxicities during treatment. Together with their short survival time, this calls for a strict indication when using cabazitaxel in patients with mCRPC.